Incompetence of Esophagie Inferior Sphincter. Their Relation with Intrathoracic and Intraabdominal Pressures - Balboa, Oscar; Delgado, Fernando; Voelker, Ricardo (Cirugía del Uruguay, 1979)
A study on esophageal manometry and pH was performed.